America's national treasures : (Mill Creek Entertainment, 2010)
In 1906, Teddy Roosevelt created the nation's first National Monument destination. The purpose was to preserve all of America's significant pieces of history. Now viewers can take a journey through the ecology, geology, and beauty of the Great Plains, the geologic West, and the historic South in an adventure never to be forgotten.